Total BIM in Swedish installation contracting; a comparative study of model-based and traditional ventilation contracting - Ahmadi, Reza (My University, 2024)
Time waste and budget overruns are common issues in most construction projects. Digital tools like Building Information Modeling (BIM) have been developed to address these problems. While BIM has improved the design process, its adoption on construction sites remains limited, where paper drawings are still dominant. Total BIM is a new concept that is becoming popular in Scandinavia and aims to use BIM models even in the production phase. This approach eliminates the need for paper drawings and has the potential to improve both project efficiency and accuracy. Therefore, this study aims to compare model-based versus traditional working methods in the production phase of a real-world installation project and analyze workers' reactions to the new concept. To conduct this comparison, the traditional workflows of an installation company were studied, and one of their ongoing ventilation projects, Blå Stjärnan, was selected as the reference project. A 3D model of the project was compiled using StreamBIM, and the company’s installers formed the study group. The comparison focused on three key areas: time spent on quantity takeoff, differences in cost estimation, and the workers’ experience with the installation process. The study also identifies several lessons and challenges related to the implementation of Total BIM. The results showed that model-based quantity takeoff improved efficiency by 40 times compared to traditional drawing-based methods. Additionally, traditional methods tended to underestimate project costs by 8% due to human errors. Workers on-site reported significant improvements in planning, efficiency, and accuracy when using the 3D model, and noted that communication through the model would have been beneficial if requirements were set. However, despite its potential, the industry remains hesitant to fully adopt Total BIM due to established workflows and the legal binding nature of paper drawings. Increased knowledge within the construction industry and successful real-world implementations could encourage clients to oblige the use of BIM models in production.
Keywords: Building Information Modelling, BIM, Cost Estimation, Digital Installation, Model-based Quantity TakeOff, Total BIM, Ventilation Contracts